Prison For Children: Education in "Un Monde" - Saul, Roger (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2024)
Un Monde, a 2021 feature film, depicts the fictional story of Nora, a child first entering school. In the film viewers are perceptually thrust into the center of Nora’s experiences – all its imagery tightly frames her against blurred school backgrounds – a harrowing exercise that compels us to encounter the traumas of her school life as she does. Drawing on Foucault’s ‘prison form,’ this review essay explores how Un Monde innovates in imagining, from the subject-position of a child, how any young person can come to be systematically severed from the relationships that matter most to them, stripped of their dignity, and rendered isolated as an unwitting prisoner of a school’s normative values and functions. It suggests that Un Monde can add to our critical vocabularies of public education by offering insights into many of the masked principles – social division, secrecy, shame, dishonesty, distrust, bystanderdism, self-preservation – that can structure relationships there.